An architectural and historical study to evaluation the operational efficiency of the Wadi Kaam Dam in the face of the effects of climate change (The International Journal of Engineering & Information Technology (IJEIT), 2026)
Dams are usually built on river courses and valleys in all countries around the world to generate electricity, and to benefit from water during non-rainfall seasons in irrigation of agricultural projects and to provide the water necessary for the daily life of humans and animals. These dams, on the other hand, pose a threat to the lives of residents living in valley streams and riverbeds if they collapse and are unable to absorb the amounts of water retained in them. This research aims to shed light on the Wadi Kaam Dam Architecturally and historically to clarify its operational efficiency and the possibility to avoid the dangers resulting from the dam not performing its function efficiently. The analytical and descriptive approach was adopted in a historical and architectural investigation of the Wadi Kaam Dam located between the cities of Zliten and Al-Khoms in Libya. The research concluded that there was some damage in the body of the dam, it is represented by the collapse of the stone layer that protects the dam from the lake side, a crack in the right shoulder of the dam, and water leakage behind the dam. The collapse and fall of stones in the spillway, the malfunction of the mechanism of movement of the water drainage gates in the intake tower and the drainage pipe, and the malfunction of the irrigation and drainage valves in the valve house and the stilling basin, some residents are building, reconstructing and farming near the course of Wadi Kaam, which may cause them great damage to life and property in the event of the dam collapsing and floods occurring. The research recommends the necessity of carrying out the necessary maintenance work for the dam and its component parts to ensure that it performs its function with high efficiency, to avoid its collapse and the occurrence of a natural disaster such as what happened in the Libyan city of Derna on September 11, 2023 AD.